2009
DOI: 10.1093/cercor/bhp129
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Selective Attention to Speech Modulates Activity in the Visual Word Form Area

Abstract: Selective attention to speech versus nonspeech signals in complex auditory input could produce top-down modulation of cortical regions previously linked to perception of spoken, and even visual, words. To isolate such top-down attentional effects, we contrasted 2 equally challenging active listening tasks, performed on the same complex auditory stimuli (words overlaid with a series of 3 tones). Instructions required selectively attending to either the speech signals (in service of rhyme judgment) or the melodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 74 publications
11
106
0
1
Order By: Relevance
“…In contrast, other studies have provided evidence that activity in the left vOT is observed during tasks other than written word recognition (Price and Devlin, 2003;Yoncheva et al, 2010). Further, phonological or semantic priming can modulate activity in the left vOT (Devlin et al, 2006), which is incompatible with its predominantly feedforward role in word recognition proposed by the LCD model.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, other studies have provided evidence that activity in the left vOT is observed during tasks other than written word recognition (Price and Devlin, 2003;Yoncheva et al, 2010). Further, phonological or semantic priming can modulate activity in the left vOT (Devlin et al, 2006), which is incompatible with its predominantly feedforward role in word recognition proposed by the LCD model.…”
Section: Introductionmentioning
confidence: 81%
“…Residual greater activity for words than digits when the task was numerical could have been due either to the greater visual complexity of the orthographical forms or to parallel implicit linguistic processing of word forms even when the explicit task was numerical. Although it might be argued, based on comments by Dehaene et al (2010) on the study of Yoncheva et al (2010), that the phonological decision on a digit elicits a stage whereby the digit is transformed internally into a visual image of its word form in the left vOT, before accessing phonology, this interpretation cannot explain why a numerical decision based on perceived word forms results in activity no greater than size decision on false font. The profile of responses we observed across conditions argues strongly that the left vOT responds to different types of objects with high spatial frequency, and the level of activity depends on the task and, perhaps, on automatic access to the language system by words regardless of the type of task.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this region is not included in two influential models of speech processing (Hickok and Poeppel, 2007;Rauschecker and Scott, 2009; but see Price, 2010) presumably because listening to speech is not typically sufficient to activate the area (Harris et al, 2009;Leff et al, 2009;Adank and Devlin, 2010). Instead tasks with a more explicit phonological component such as rhyme (Booth et al, 2004;Seghier et al, 2004;Yoncheva et al, 2010) or syllable judgments (Price et al, 1997;Callan et al, 2003;Devlin et al, 2003;Zevin and McCandliss, 2005;Raizada and Poldrack, 2007) activate the region. One thing that may be common across these tasks is a covert articulation of the stimulus, consistent with the strong anatomical connections linking SMG to ventral premotor cortex (PMv) (Catani et al, 2005;Petrides and Pandya, 2009) where neurons control oro-facial movements of the lips, tongue, and larynx and play an important role in articulation (Petrides et al, 2005;Sereno and Dick, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of verbal working memory commonly implicate these regions (Paulesu et al, 1993;Romero et al, 2006;Koelsch et al, 2009). It is worth noting that reproducible sounds are not limited to verbal information-when subjects attend to reproducible sequences of tones, for instance, activation is also seen in these areas (Gelfand and Bookheimer, 2003;Yoncheva et al, 2010). Second, this type of anatomical loop provides a computational mechanism for encoding statistical regularities among components of the representation which help to "clean up" aberrant patterns of activity via attractor dynamics (Pearlmutter, 1989;Amit, 1992;Lundqvist et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation